Protection and Response of a Tertiary Hospital in South Korea to the COVID-19 Outbreak - Shi, Hye Jin (Disaster Med Public Health Prep, 2020)
OBJECTIVE: Here, we present an overview of how a tertiary hospital responded to maintain necessary activities and protect patients and staff from the coronavirus disease (COVID-19) outbreak. METHODS: Gil Medical Center, a tertiary hospital in Incheon, has operated a special response team since January 21, 2020. All visitors were assessed for body temperature and respiratory symptoms, and screened for recent overseas travel. Suspected COVID-19 patients were taken to a screening clinic. All febrile patients with or without respiratory symptoms were taken to a respiratory safety clinic. An isolation ward, which consisted of 10 negative-pressure rooms, was used to treat confirmed cases. More than 120 beds were prepared for the outbreak, and patients with pneumonia were preemptively isolated. RESULTS: By May 5, 480 960 visitors were assessed at the control station, 3350 patients visited the triage center, and 1794 were treated in the respiratory safety clinic. Seventeen confirmed cases were admitted to the negative isolation ward, and 350 patients with pneumonia were preemptively isolated. A total of 2977 severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) polymerase chain reaction tests were performed. CONCLUSIONS: While tertiary hospitals play an important role in treating both COVID-19 patients and non-COVID-19 patients, hospital staff have to protect themselves from unexpected in-hospital transmission. A multifaceted response must be undertaken to protect tertiary hospitals and their staff during the COVID-19 epidemic.